If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4 = 4x + 4 Reorder the terms: 4 + 5x = 4x + 4 Reorder the terms: 4 + 5x = 4 + 4x Add '-4' to each side of the equation. 4 + -4 + 5x = 4 + -4 + 4x Combine like terms: 4 + -4 = 0 0 + 5x = 4 + -4 + 4x 5x = 4 + -4 + 4x Combine like terms: 4 + -4 = 0 5x = 0 + 4x 5x = 4x Solving 5x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5x + -4x = 4x + -4x Combine like terms: 5x + -4x = 1x 1x = 4x + -4x Combine like terms: 4x + -4x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| X+7=34 | | 2x+10=4x-4 | | 408=10x+22 | | 3(y+6)-y=2(y-9) | | 2(5-x)=4x | | (2x+5)(4x-2)=(2x)(4x) | | (2x+5)(4x-2)=(2x)(4x)+(2x)(-2)+(5)(4x)+(5)(-2) | | -15x^2+11x-2=0 | | 12x^2+13x-30=0 | | 6x^2-11x+2=0 | | ln(x)-ln(x-7)=ln(2) | | ln(x)-ln(x-7)=ln(2) | | 30r^2-13r-3=0 | | 30t^2-49t+20=0 | | 589270957349857476-4= | | 12x^2+5-23x=0 | | 3(4x+5)=63 | | 5x^2-6x+4=0 | | 3a+8=20 | | 2a+9=17 | | a+1=4 | | X(3)=12 | | 16x-8y=64 | | 4(3q+7)=7 | | 7x+38=-4 | | 11(16-g)=22 | | f=-2f-9 | | -84-8x=9x+18 | | 156-7x=29x+24 | | 145-6x=3x+10 | | 8f=-2f-10 | | 9x=125 |